ACTIVITY-BASED COSTING IN THE MANUFACTURING SECTOR: A MANAGERIAL INSTRUMENT FOR DECISION-MAKING - Ioana D. BUFAN (SEA: Practical Application of Science, 2014)

(untitled)
The aim of this paper is to emphasize the importance of using the activity-based costing (management) system in the manufacturing sector. The utility of the ABC (ABM) system concerns decisions taken at a strategic and operational level. In our country, few managers understand the need for such a system and many Romanian companies use only a traditional costing system or don’t use one at all. The paper also includes a case study which is a small example of using the ABC method in a Romanian manufacturing company. The study shows that the ABC/ABM system helps managers to properly manage indirect costs (by activities) and understand the profitability of products, distribution channels and customers. Therefore, it offers a powerful instrument for decision-making. Although ABC is a new system of cost calculation that is absolutely necessary, in most cases the ABC method must be implemented in addition to the traditional costing systems, which are essential for the purposes of management accounting.